Transfer of dislocation slip through grain boundaries in metal-graphene nanocomposites. (1st April 2022) - Mikaelyan, K.N.; Sheinerman, A.G.
Graphical abstract: Highlights: The onset of plastic deformation in metal-graphene nanocomposites is modeled. Plastic deformation occurs via dislocation transmission across grain boundaries. Expanding dislocation loops bypass graphene platelets at grain boundaries. This increases the yield strength of metal-graphene composites. Abstract: A model is suggested that describes the onset of plastic deformation in metal-graphene nanocomposites. Within the model, the plastic deformation of a deformed metal-graphene nanocomposite is realized through the generation of perfect or partial dislocation loops. These loops nucleate at grain boundaries (GBs) of the metallic matrix and expand across grains. The expanded dislocation loops promote the nucleation and expansion of secondary dislocation loops in adjacent grains, thereby realizing dislocation transmission across GBs. Within the model, we have calculated the critical stresses, τ c 1 and τ c 2, for the generation of a secondary perfect or partial dislocation loop and for the bypass of the graphene inclusion by the secondary loop. The critical stress τ c 2 increases with an increase in the graphene concentration and with a decrease in the thickness of the inclusion. This implies that the addition of graphene can raise the critical stress for the expansion of the secondary dislocation loops and thus increase the yield strength of metals.